Bevacizumab plus Capecitabine as Maintenance Therapy after Initial Bevacizumab plus XELOX Treatment in Previously Untreated Patients with Metastatic Colorectal Cancer: Phase Ill 'Stop and Go' Study Results - A Turkish Oncology Group Trial - DANE, FAYSAL (KARGER, 2013)
Objective: It was the aim of this study to evaluate maintenance therapy with bevacizumab + capecitabine following induction with bevacizumab + capecitabine + oxaliplatin (XELOX) versus bevacizumab + XELOX until progression as first-line therapy in metastatic colorectal cancer (mCRC). Methods: Patients received either bevacizumab (7.5 mg/kg) + XELOX (capecitabine 1,000 mg/m(2) twice daily on days 1-14 + oxaliplatin 130 mg/m2 on day 1 every 3 weeks) until disease progression (arm A) or the same doses of bevacizumab + XELOX for 6 cycles followed by bevacizumab + capecitabine until disease progression (arm B). The primary endpoint was progression-free survival (PFS); secondary endpoints included overall survival (OS), objective response rate (ORR) and safety. Results: One hundred and twenty-three patients were randomized. Treatment compliance was similar in both groups. Median PFS was significantly longer for arm B than for arm A (11.0 vs. 8.3 months; p = 0.002). There was no significant difference between the two arms for ORR (66.7 vs. 59.0%; p = 0.861) or median OS (23.8 vs. 20.2 months; p = 0.100). Tolerability was acceptable in both treatment arms; the most frequent grade 3/4 treatment-related adverse events (arm B vs. arm A) were fatigue (6.6 vs. 16.1%), diarrhoea (3.3 vs. 11.3%), anorexia (3.3 vs. 11.3%), and neuropathy (1.6 vs. 8.1%). Conclusions: Maintenance therapy with bevacizumab + capecitabine can be considered an appropriate option following induction bevacizunnab + XELOX in patients with mCRC instead of continuation of bevacizumab + XELOX. (C) 2013 S. Karger AG, Basel
Keywords: Bevacizumab; Capecitabine; Oxaliplatin; Metastatic colorectal cancer; Maintenance therapy; 1ST-LINE THERAPY; FINAL REPORT; OXALIPLATIN; FLUOROURACIL; CHEMOTHERAPY; LEUCOVORIN; COMBINATION; EFFICACY; INTERMITTENT; FOLFOX4